2018
DOI: 10.1186/s12881-018-0614-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of KCNQ1, CDKN2A/2B, CDKAL1, HHEX, MTNR1B, SLC30A8, TCF7L2, and UBE2E2 on risk of developing type 2 diabetes in Thai population

Abstract: BackgroundSeveral type 2 diabetes (T2D) susceptibility loci identified via genome-wide association studies were found to be replicated among various populations. However, the influence of these loci on T2D in Thai population is unknown. The aim of this study was to investigate the influence of eight single nucleotide polymorphisms (SNPs) reported in GWA studies on T2D and related quantitative traits in Thai population.MethodsEight SNPs in or near the KCNQ1, CDKN2A/2B, SLC30A8, HHEX, CDKAL1, TCF7L2, MTNR1B, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 44 publications
0
17
0
1
Order By: Relevance
“…In contrast, a study reported that WHR was significantly linked with CDKN2A/2B (rs10811661) risk allele among T2DM cases in the Chinese Han population with p = 0.032. 10 CDKN2A/2B gene may influence the risk of T2DM by decreasing the expression and proliferation of beta-cell. 23 IGF2BP2 gene has been recognized to be linked with reduced secretion of insulin and it has a significant role in T2DM pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a study reported that WHR was significantly linked with CDKN2A/2B (rs10811661) risk allele among T2DM cases in the Chinese Han population with p = 0.032. 10 CDKN2A/2B gene may influence the risk of T2DM by decreasing the expression and proliferation of beta-cell. 23 IGF2BP2 gene has been recognized to be linked with reduced secretion of insulin and it has a significant role in T2DM pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Advancement in genomic data and technology have helped the genome-wide association studies (GWAS) in recognizing the susceptible genes of T2DM. 10 Numerous GWAS confirmed the association of susceptible genes with T2DM in or near CDK5 Regulatory Subunit Associated Protein 1-Like 1 (CDKAL1), PPARG, Solute Carrier Family 30 Member 8 (SLC30A8), TCF7L2, Melatonin Receptor 1b (MTNR1B), Potassium Voltage-Gated Channel, KQT-Like Subfamily, Member 1 (KCNQ1), Wolframin ER Transmembrane Glycoprotein (WFS1), Hepatocyte Nuclear Factor 1 Homeobox B (HNF1B), Cyclin-Dependent Kinase Inhibitor 2A (CDKN2A/2B), Insulin-Like Growth Factor 2 mRNA Binding Protein 2 (IGF2BP2), and Juxtaposed with Another Zinc Finger Protein 1 (JAZF1) among Asian and European population. [10][11][12] Chiefari et al studied the highmobility group A1 (HMGA1) gene variants in T2DM patients and controls in 3 populations of white European ancestry and found the association of functional HMGA1 variants in people with T2DM of European ancestry.…”
Section: Introductionmentioning
confidence: 99%
“…However, in our study we did not observed any association between the rs7923837 and T2DM(P = 0.181) which may be explained by different environmental risk pro les between Europeans and Asians, different body composition and genetic backgrounds, different linkage disequilibrium patterns. This possibility also be supported by association study done for Thai population in 2018, Plengvidhya, N. et al found that no signi cant association could be concluded between rs7923837 on HHEX and T2DM [38].…”
Section: Discussionmentioning
confidence: 77%
“…Below we provide a comprehensive review of these aspects with a particular focus on T2D. GWAS and replication studies have shown that polymorphic variants within the CD-KAL1 locus are strongly associated with increased T2D risk and reduced insulin secretion in different populations [83,84,[99][100][101][102][103][104][105][106][107][108][109][110]. All disease-associated SNPs are located in intron 5 of CDKAL1 [83].…”
Section: Dysregulated Trna Metabolism In Diabetesmentioning
confidence: 99%